2016
DOI: 10.1016/j.msea.2015.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue life and fracture mechanics of unconstrained Ni–Mn–Ga single crystals in a rotating magnetic field

Abstract: a b s t r a c tFracture resistance and long fatigue life are required to commercialize Ni-Mn-Ga ferromagnetic shape memory alloys. While Ni-Mn-Ga achieves high fatigue life at low strains, there is little data on the fatigue life of samples that are actuated near the theoretical strain limit. Furthermore, constraints imposed by clamping samples impact their magneto-mechanical and fatigue properties. Here, 10 M Ni-MnGa single crystals were exposed to a rotating magnetic field while holding them with rubber O-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Since the first observation of the magnetic field induced strain in Ni2MnGa by Ullakko [1], the ferromagnetic shape memory alloys (FSMAs) have attracted a great attention as a kinds of intelligent material for actuator and sensor. In past two decades, based on twin martensite variants remigration, numerous FSMAs, such as Ni-Mn-Ga [2][3][4], Co-Ni-Al [5,6], Mn-Ni-Sn [7], and Ni-Fe-Ga [8,9], achieved 8-10% giant stain. However, the actuator and sensor made of FSMAs did not get a wide range of applications due to their low phase transition temperature and poor mechanical properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first observation of the magnetic field induced strain in Ni2MnGa by Ullakko [1], the ferromagnetic shape memory alloys (FSMAs) have attracted a great attention as a kinds of intelligent material for actuator and sensor. In past two decades, based on twin martensite variants remigration, numerous FSMAs, such as Ni-Mn-Ga [2][3][4], Co-Ni-Al [5,6], Mn-Ni-Sn [7], and Ni-Fe-Ga [8,9], achieved 8-10% giant stain. However, the actuator and sensor made of FSMAs did not get a wide range of applications due to their low phase transition temperature and poor mechanical properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…In MSM-polymer hybrids the MSM particles are embedded in the polymer matrix and bonded to the matrix, the strength depending on the adhesion properties of the polymer with MSM. It has been reported that the brittleness of Ni-Mn-Ga may cause cracks into the material [12]. In such a case the polymer would hold the structure together and a hybrid component could be still usable despite of the cracks.…”
Section: Introductionmentioning
confidence: 99%
“…In (b) the sample has twinned in response to the field, now taking a different field pattern, the field lines slightly deflected by twin boundaries [89]. Reprinted from Scripta Materialia, 77 (1) was attached to the sample holder (2) by double-sided tape. The tube (4) coupled to the HD camera (5), which recorded the reflection of sample through a mirror (3) while these components were rotated in the magnetic field (6) by a sequence-controlled motor.…”
mentioning
confidence: 99%